2010
DOI: 10.1007/s00396-009-2169-y
|View full text |Cite
|
Sign up to set email alerts
|

Templated assembly of polymer particles into mesoscopic clusters with well-defined configurations

Abstract: We report on the fabrication of colloidal clusters through the combination of spherical particles. Polystyrene latex particles bearing amino groups on their surface were used as building blocks of the clusters. Packing of these particles with diameters of 91 and 154 nm into assemblies with defined configurations was accomplished using narrow dispersed emulsion droplets as templates. The building blocks of the clusters adhered to the oil-water interphase due to the Pickering effect. Subsequent evaporation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 47 publications
(65 reference statements)
7
54
1
Order By: Relevance
“…6(c)] such as n c = 4, n b = 6 (tetrahedron); n c = 6, n b = 12 (octahedron); n c = 8, n b = 18 (snub disphenoid); n c = 10, n b = 22 (gyreoelongate square dipyramid). These structures are similar to the onecomponent structures that minimize the second moment of the mass distribution [20,23]. Figure 7 shows a stacked histogram of the number of clusters N nc with n c colloids.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…6(c)] such as n c = 4, n b = 6 (tetrahedron); n c = 6, n b = 12 (octahedron); n c = 8, n b = 18 (snub disphenoid); n c = 10, n b = 22 (gyreoelongate square dipyramid). These structures are similar to the onecomponent structures that minimize the second moment of the mass distribution [20,23]. Figure 7 shows a stacked histogram of the number of clusters N nc with n c colloids.…”
Section: Resultsmentioning
confidence: 83%
“…Based on this technique, Manoharan et al [20] successfully prepared micrometer-sized clusters and found that the structures of particle packings seem to minimize the second moment of the mass distribution. Wittemann et al also produced clusters, but with a considerably smaller size of about 200nm [21][22][23]. Cho et al prepared binary clusters with different sizes or species from phase-inverted water-in-oil [24] and oil-in-water emulsion droplets [25].…”
Section: Introductionmentioning
confidence: 99%
“…The size distribution of the templating emulsion droplets was controlled by ultrasound [39]. Evaporation of the dispersed phase creates capillary forces which pack the particles together into clusters that exhibit well-defined configurations, such as particle doublets, triplets, tetrahedrons, triangular dipyramids, and octahedrons, among others [32]. Because the dispersed phase presents a solvent for polystyrene, the cluster constituents are swollen during the assembly.…”
Section: Resultsmentioning
confidence: 99%
“…[32,39]. The cluster preparation is based on the agglomeration of the constituent particles while adsorbed onto the surface of emulsion droplets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation